2021
DOI: 10.3390/pathogens10101336
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Terahertz Time-Domain Spectroscopy to Identification of Potato Late Blight and Fusariosis

Abstract: Fusarium and late blight (fungal diseases of cereals and potatoes) are among the main causes of crop loss worldwide. A key element of success in the fight against phytopathogens is the timely identification of infected plants and seeds. That is why the development of new methods for identifying phytopathogens is a priority for agriculture. The terahertz time-domain spectroscopy (THz-TDS) is a promising method for assessing the quality of materials. For the first time, we used THz-TDS for assessing the infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Real-time PCR. Primer specific for these pathogen was used to identify Fusarium graminearum in the respective samples (F-5 -GTTGATGGGTAAAAGTGTG-3 ; R-5 -CTCTCA TATACCCTCCG-3 , Intergenic Spacer of rDNA (IGS region)) [12]. Primer was synthesized at the QuantStudio TM 5 Real-Time PCR System (Thermo Fisher, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Real-time PCR. Primer specific for these pathogen was used to identify Fusarium graminearum in the respective samples (F-5 -GTTGATGGGTAAAAGTGTG-3 ; R-5 -CTCTCA TATACCCTCCG-3 , Intergenic Spacer of rDNA (IGS region)) [12]. Primer was synthesized at the QuantStudio TM 5 Real-Time PCR System (Thermo Fisher, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…LWIR imaging and terahertz spectroscopy are often used to assess water movement in plants, through root uptake and leaf transpiration through stomata. Diseases caused by fungi and oomycetes can interfere with transpiration, enabling plant disease diagnosis by thermal infrared imaging [180] as well as terahertz time-domain spectroscopy [181]. Thermal imaging has also been used to detect pests in stored grains due to animal respiration [182] and damage to guava fruit caused by disease [183].…”
Section: Infrared (Thermal) Imagingmentioning
confidence: 99%
“…It has been shown that the THz-TDS method makes it possible to assess the degree of Fusarium infection in cereal seeds (oats, wheat and barley) and late blight in potato tubers. Changes are observed in refractive indices, absorption coefficients and dielectric functions in healthy and infected plants [155]. Terahertz imaging has also been used to identify fungal infections in chestnut trees [156], powdery mildew in tomato leaves [157] and wheat mold [158].…”
Section: Terahertz Time-domain Spectroscopymentioning
confidence: 99%